2011
DOI: 10.3109/01942638.2011.631100
|View full text |Cite
|
Sign up to set email alerts
|

Social Participation of Adolescents with Cerebral Palsy: Trade-offs and Choices

Abstract: This article reports on the findings of a qualitative study about the experiences and perceptions of adolescents with cerebral palsy (CP) in relation to social participation. A phenomenological approach was used to interview 10 adolescents with CP, 17 to 20 years of age, selected using purposeful sampling. An iterative process of data collection and analysis resulted in four themes about social participation. The themes of experience, barriers, and supports, and tradeoffs supported the current view of particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 26 publications
1
22
0
2
Order By: Relevance
“…Furthermore, service providers should recognize that regardless of disability, a person's preferences may change over time, especially as they progress into young adulthood. This recommendation is related to the findings of the ASQME study (Stewart et al, 2012), where much of what the adolescent participants with CP had to say about their experiences in activity engagement were typical of youth of any background or ability. This idea was confirmed by youth and parent participants in the current study, who reported that youth with CP just want to have the same opportunities as everyone else.…”
Section: Discussionmentioning
confidence: 93%
“…Furthermore, service providers should recognize that regardless of disability, a person's preferences may change over time, especially as they progress into young adulthood. This recommendation is related to the findings of the ASQME study (Stewart et al, 2012), where much of what the adolescent participants with CP had to say about their experiences in activity engagement were typical of youth of any background or ability. This idea was confirmed by youth and parent participants in the current study, who reported that youth with CP just want to have the same opportunities as everyone else.…”
Section: Discussionmentioning
confidence: 93%
“…Other researchers have discussed various factors affecting choice of activity, including making trade-offs [6], apprehension related to activity performance and participation [16], issues of gaining entry [17], and the gaining competency by engaging in fun and important activities [1]. Youth in our study explicitly mentioned trade-offs, wanting to engage in fun activities, and apprehension or worry about factors such as transportation.…”
Section: Youth Experiences Of Activity Settings 19mentioning
confidence: 84%
“…Another direction of interest, highlighted by our awareness that participation is intimately tied to context [3] and our concerns about the meaning of our findings, is the selection of leisure activity settings. Research studies, including ours, have focused on how the environment affects child/youth opportunities and experiences, but little work, other than that by Stewart et al [6] on trade-offs, has examined this relationship in the other direction. Work on psychological selection has linked the selection of activities to the 'anticipation' of experience and optimal experience [1,44].…”
Section: Research Implicationsmentioning
confidence: 91%
See 1 more Smart Citation
“…These authors stressed the importance of acknowledging children as active agents negotiating their everyday interactions with peers, adults and services. Their contribution has influenced researchers who increasingly seek the perspectives of children and youth Disability & Society 1077 (Egilson and Traustadóttir 2009a;Egilson and Hemmingsson 2009;Eriksson, Welander, and Granlund 2007;Stalker 2012;Stewart et al 2012). In this context it is of interest to explore how youth with physical impairments understand and interpret their present and past school experiences through a longitudinal lens.…”
Section: Theoretical Approachmentioning
confidence: 99%